Analysis of the Utilization of Sugar Palm as a Raw Material for Palm Sugar and Alcohol Production in Manembo Village - Hendra Amon; Zibran Poli (Jurnal Hutan dan Masyarakat, 2025)
The excellent potential of sugar palm in Manembo Village, East Passi District, Bolaang Mongondow Regency has led the community to utilize them as raw materials for producing palm sugar and alcohol, which serve as sources of income to increase community income. However, there is currently no detailed data, information, or analysis on the utilization of palm trees by the Manembo Village community in terms of producing raw materials for palm sugar and alcohol to increase community income. The purpose of this study is to analyze the utilization of sugar palm (Arenga pinnata Merr) as a raw material for making palm sugar and alcohol to increase community income in Manembo Village. This study employs a survey method with data collection techniques including interviews, questionnaires, and direct field observations. Data analysis involves both quantitative and qualitative descriptive methods, as well as tabulation of the benefits of the sugar palm, the parts utilized, types of utilization, and income generated from sugar palm-based enterprises. The results indicate that the community utilizes the sugar palm’s trunk to extract palm water sap as a raw material for producing palm sugar and alcohol. The community processes palm sugar and alcohol, 85% for commercial purposes and 15% for subsistence (personal consumption). The net income earned by the residents of Manembo village amounts to Rp 2,668,500 per month per household.